RELASI GREEN PADA GAMMA-SEMIGRUP YANG DIBANGKITKAN DARI SUATU SEMIGRUP - YD Sumanto; Abdul Aziz; Solikhin Solikhin; R. Heri Soelistyo Utomo (Journal of Fundamental Mathematics and Applications (JFMA), 2020)
In the Gamma-semigroup generated from a semigroup, we can define some equivalence relations called the Green relation. Furthermore, we can examine the relationship between the Green relation on the Gamma-semigroup and the Green relation on it’s generating semigroup.